PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA PURWABAKTI, KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Rizal, Muhammad; Pulungan, Adilah Rahma (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
This community service aims to increase community knowledge and understanding of sharia financial planning for families in Purwabakti Village, Pamijahan District, Bogor Regency. In this community service, activities are carried out based on the descriptive method, and the implementation of outreach activities uses interview, observation and documentation data collection techniques. The result of this community service shows that public knowledge about family financial planning is still low. With this service to the community, it can be concluded that community outreach is a good step for the community so that those who are married can carry out good family financial planning in order to make their family prosperous.